Collaborative teaching and learning of interactive multimodal spoken academic genres for doctoral students - Querol-Julián, Mercedes; Fortanet-Gómez, Inmaculada (International Journal of English Studies, 2019)
The last teaching-learning stage in the education system is the doctoral programmes, which turn graduate students into researchers. This evolution involves writing a dissertation, but also being able to discuss research. However, training on spoken genres has not received much attention, and the interest has been mainly on monologic prepared speeches. This paper focuses on a genre of interactive speech, the discussion session (DS) that follows the paper presentation, which is particularly challenging for novice researchers. We present a learner-led pedagogy for the teaching-learning of this genre that fosters thinking-based learning and multimodal awareness. It was implemented in a course of academic discourse for doctoral students in order to prove its effectiveness. We propose a process of active and collaborative deconstruction and construction of DSs to identify verbal and non-verbal resources and their interpersonal functions, so that novel researchers reflect on and integrate them in their repertoire.